2020
DOI: 10.1016/j.diabres.2020.108074
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a foot temperature monitoring mat for predicting diabetic foot ulcers in patients with recent wounds or partial foot amputation

Abstract: To assess the accuracy of once-daily foot temperature monitoring for predicting foot ulceration in diabetic patients with recent wounds and partial foot amputation, complications previously perceived as challenging. Methods: We completed a planned analysis of existing data from a recent study in 129 participants with a previously-healed diabetic foot ulcer. We considered four cohorts: all participants, participants with partial foot amputation, participants with a recent wound, and participants without partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
0
21
0
4
Order By: Relevance
“…Accuracy of this approach using the study device previously has been reported to predict 97% of non-acute plantar DFU in patients in diabetic foot remission, 21 and a recent study found no difference in accuracy for those with partial foot amputations. 22 The mat form factor of the study device accommodates patients with foot deformity and partial-foot amputations.…”
Section: Study Programmentioning
confidence: 99%
“…Accuracy of this approach using the study device previously has been reported to predict 97% of non-acute plantar DFU in patients in diabetic foot remission, 21 and a recent study found no difference in accuracy for those with partial foot amputations. 22 The mat form factor of the study device accommodates patients with foot deformity and partial-foot amputations.…”
Section: Study Programmentioning
confidence: 99%
“…16 Various studies have looked at a temperature monitoring mat that can be kept at a patient's home. [16][17][18] Frykberg et al studied 129 patients who used the mat and found high adherence, with 86% of individuals measuring their plantar temperature an average of three times a week, and 88% stating the mat was easy to use. Additionally, researchers found that 97% of all DFUs were found with the thermography mat, and on average they were detected 37 weeks before they were detected in person, in the clinic.…”
Section: Diabetic Foot Ulcer Monitoringmentioning
confidence: 99%
“…Physical examinations of feet and eyes are still necessary in-person today, though there are already a number of commercialized technologies to monitor for foot ulcers (e.g., Podimetrics 12 ), and researchers aspire to develop reliable retinopathy assessments from non-mydriatic smartphone camera images in the not-too-distant future 13 . Even with these developments, most people with diabetes will benefit from occasional in-person visits in addition to participation in a virtual clinic.…”
Section: Classification Schema For Connected Diabetes Carementioning
confidence: 99%